Detrital zircon U-Pb age and detrital rutile trace element data from the late Neogene Baode Red Clay sequence, Chinese Loess Plateau, and detrital rutile geochemistry from 14 potential source areas - Katja Bohm; Anu Kaakinen; Thomas Stevens; Yann Lahaye; Hugh O extquotesingleBrien; Hui Tang; Yuan Shang; Hanzhi Zhang; Huayu Lu (PANGAEA, 2023)
The data were collected for a joint detrital zircon and detrital rutile provenance study of the late Neogene aeolian Baode Red Clay, located on the northern part of the Chinese Loess Plateau. The data consist of detrital zircon U-Pb ages of the 4.04–2.64 Ma Baode Red Clay (four samples from the Pliocene Jingle Formation and one sample from the 2.64 Ma Transitional Unit), and detrital rutile trace element geochemistry of the 6.91–2.64 Ma Baode Red Clay (three samples from the Miocene Baode Formation, five samples from the Pliocene Jingle Formation, and one sample from the Transitional Unit) and 14 potential sedimentary source areas in Central-East Asia. The data were collected using Nu Plasma AttoM single collector ICP-MS (Nu Instruments Ltd., Wrexham, UK) connected to an Analyte Excite 193 ArF laser ablation system (Photon Machines, San Diego, USA) at the Geological Survey of Finland. The rutiles were analysed for Li, Mg, Al, Si, P, Ca, Sc, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Rb, Sr, Y, Zr, Nb, Mo, Sn, Sb, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Hf, Ta, W, Pb, Th, and U. The grain size fractions of the analysed grains were mostly 30–90 μm for the Red Clay zircons and rutiles, and 20–500 μm for the potential source area rutiles.